2015
DOI: 10.1080/02650533.2015.1092952
|View full text |Cite
|
Sign up to set email alerts
|

The wellbeing of foster children and their relationship with foster parents and biological parents: a child’s perspective

Abstract: Most Dutch foster children live permanently in foster families. It is often assumed that foster children have ambivalent loyalties and attachments to their birth parents and foster parents and are torn between the two. In this study 59 children between 10 and 18 years placed in long term foster care completed standardised questionnaires on the relationship with their parents respectively foster parents and their wellbeing. Results show that, on average, foster children have positive feelings of loyalty and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 44 publications
0
18
0
3
Order By: Relevance
“…Drawing on previous research (Maaskant et al, 2016), it can be supposed that children who were placed in foster care as infants have had fewer opportunities to build relationships with their birth parents. Consequently, the contact with birth parents might be less significant for children who have been in foster care since they were very young.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on previous research (Maaskant et al, 2016), it can be supposed that children who were placed in foster care as infants have had fewer opportunities to build relationships with their birth parents. Consequently, the contact with birth parents might be less significant for children who have been in foster care since they were very young.…”
Section: Discussionmentioning
confidence: 99%
“…We do not find evidence which suggested that the young people interviewed felt torn between birth parents and foster parents. Following Maaskant, van Rooij, Bos, and Hermanns (2016), this can be interpreted as the young people in our study were not particularly worried about their birth parents and that they had stable relationships with their new custodians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a widespread view that contact with parents leads to shorter stays in foster care, but Nina Biehal (2007) demonstrates in her research review that the connection between contact and reunification is complex and should not to be understood as a causal connection. A close relationship with foster parents may not interfere with a child's wish to keep in contact with birth parents (Atwool, 2013;Baker et al, 2016;Fernandez, 2007;Maaskant, van Rooij, Bos, & Hermanns, 2016). It is also true that contact with parents is problematic for some children in foster care and some children do not want to stay in contact (Lundström & Sallnäs, 2009;McWey, Acock, & Porter, 2010;Moyers et al, 2006).…”
Section: Glimpses From Other Research On Relationships To Parentsmentioning
confidence: 99%
“…Other research findings have emphasized that well-being is dependent on the quality of the caregiver-child relationship, as well as placement stability (Dolbin-Macnab & Keiley, 2009;Goodman, 2012). Literature further suggests that kinship care in Western contexts, whether formal or informal, often arises following parental neglect, abuse or engagement in illegal activities (Gibson & Singh, 2010;Gleeson et al, 2009;Lee, Clarkson-Hendrix, & Lee, 2016;Maaskant, van Rooij, Bos, & Hermanns, 2016;Patterson et al, 2018). These experiences infer an increased probability of traumatic experiences within the initial parent-child relationships, prior to kinship care.…”
Section: Rationalementioning
confidence: 99%